Strategi Digital Marketing Dalam Pengembangan Akun Kreator PT. Uplus Technology Indonesia - Achmad Razif Zahira; Anisa Diniati (Universitas Telkom, 2024)
TikTok is a social media that is growing very rapidly, becoming one of the most frequently used daily social media. Tiktokcurrently has 1 billion active users in Indonesia, with an average of 26 hours a day spent on the TikTok application. Withsuch user data, TikTok, which has opened selling or e-commerce services, has become very trending, apart from enjoyingshort video entertainment uploads, now users can shop quickly in the TikTok application. Of course, with the sales andincome in tiktok, competition is inevitable, MCN (multi-channel networking) tiktok has sprung up to attract creators from allover Indonesia to plunge into the livelihood of the tiktok application. This research uses the theory of marketing strategy,namely AIDA. This research uses qualitative research with descriptive research type, and data collection techniques withfield observations, interviews with one key informant, one expert informant, and one supporting informant, and documentstudies. The results showed that the marketing strategy used by P.T. Uplus Technology Indonesia is very efficient in usingAIDA theory in short-term or long-term marketing. The use of other sales strategies such as anchoring, time-limit, andscarcity also support the sales and increase of creator accounts held by uplus. The final conclusion is that P.T. Uplusmanaged to maximize its marketing strategy well so that the potential of each account can be maximized by driving salesand awareness through short video uploads and live rooms.